From international conventions to local park management plans : an analysis of the vertical integrity of Zambia's national park system : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Environmental Management at Massey University, New Zealand - Mwape, Ackim (Massey University, 2018)
National parks, particularly in the Global South, are struggling to achieve their economic, ecological, and socio-cultural objectives and their sustainability is now in question. The challenges faced by national parks cross jurisdictional boundaries, cutting through vertical tiers of governance, from supranational organisations, via national governments, to sub-national entities. Given this complexity, it is extremely challenging to make system-wide improvements. Sustainable national park management requires whole-of-government approaches and policy consistency across different governance levels. Aligned policy frameworks are essential for achieving consistency, driving collaboration, and, ultimately, coherence where subnational actors work together with other actors to achieve common goals towards global Challenges. Examining the alignment of policies used across the different governance levels could provide information to help improve sustainable national park management. This study focuses on Zambia’s national park laws, policies, plans, and reports, and particularly how these align with international principles for national park management. Thematic content analysis is used to examine how a set of IUCN national park management principles are considered in Zambia’s national park legislation, policies, plans, and reports. The results reveal wide variation in the extent to which Zambia’s national park laws, policies, plans, and reports reflect the IUCN principles. They highlight isolated outcomes of positive alignment with the IUCN principles both at national and local level, amidst a general picture of uneven support for the IUCN principles. This is because international principles are introduced, or interpreted, contingent on specific local conditions, making it difficult for policymakers to develop local policies that mirror global policy models. A balance between the respect for international principles and an understanding and appreciation of the local context thus appears to be a way for strengthening policy linkages Between the global and local. International and local level policymakers retain an important responsibility in this regard.
Reproduction of Appendix A © 2011 International Union for Conservation of Nature and Natural Resources is authorized without prior written permission from the copyright holder provided the source is fully acknowledged: Lausche, Barbara. (2011). Guidelines for Protected Areas Legislation. IUCN, Gland, Switzerland. xxvi, 371 pp.
Keywords: National parks and reserves; Zambia; Management; Sustainable development; 410404 Environmental management